Socio-Economic Mobility of Development Towns in Israel - Momi Dahan (CESifo GmbH, 2025)
This study reveals that, over the past six decades, development towns have improved their socio-economic status both in terms of absolute mobility (compared to their past position) and relative mobility (progressing at a faster rate than other Jewish cities and towns). Between 1961 and 2019, economic mobility was evident in the narrowing gap between development towns and non-development towns (NDT) across five key economic development indicators: population size, median age, education level, income per capita, and ranking on a socioeconomic index. Despite this progress, development towns remain, on average, below the median socio-economic ranking. The empirical analysis also provides measures of absolute and conditional convergence. It demonstrates that the change in socio-economic rankings between 1961 and 2019 was more significant in localities that were ranked lower in 1961. The degree of conditional convergence was even more substantial when differences in the characteristics of the localities were accounted for. This paper shows that the two standard measures of immobility and convergence which appear in two separate literatures are in fact interconnected, representing two sides of the same coin. I speculate that the reduction in socioeconomic inequality between development towns and NDT can be attributed to factors such as free universal public education, Israel's advanced healthcare system, and cultural diffusion resulting from interactions with the host population.
Keywords: J62; N95; R11; R58; 330; development towns; mobility; economic convergence